The Use of Excess Cash and Debt Capacity as a Motive for Merger - Bruner, Robert F. (Journal of Financial and Quantitative Analysis, 1988)
This study explores the hypothesis that capital structure change provides bidders and targets a motive for merger. After a brief review of theories that would support the hypothesis, the paper reports results of tests on (1) leverage in bidder and target firms, and (2) change in shareholder wealth associated with change in leverage. The findings support the theory of Myers and Majluf that “slack-rich” bidders pair with “slack-poor” targets to create value. These results are contrary to other studies, which find highly levered bidders.